Subjective symptoms in Magnetic Resonance Imaging operators: prevalence, short-term evolution and possible related factors - Zanotti, Giulio; Ligabue, Guido; Korpinen, Leena; Gobba, Fabriziomaria (La Medicina del Lavoro, 2016)
Background: The number of Magnetic Resonance Imaging (MRI) operators is rapidly increasing. In these workers, a high prevalence of certain subjective symptoms has been described but until now scant research is available on this topic. Objectives: To assess the prevalence and the evolution of symptoms over time in a group of operators recently engaged in MRI, also considering the possible role played by factors such as age, gender and occupational stress. Methods: In 17 physicians exclusively engaged in MRI - 6 working with 1.5 T scanners only and 11 with both 1.5 and 3T - subjective symptoms were evaluated at the beginning of MRI activity and after 2 months by using an ad hoc questionnaire. The questionnaire also included items on occupational stress. Results: At the start of MRI activity, 81% of the subjects reported at least one of the investigated symptoms; after 2 months, 85% of the symptomatic operators reported the regression of one or more symptoms. In operators with high exposure (1.5 and 3 T scanners), the mean number of symptoms tended to be higher compared with those with lower exposure (1.5 T only), and the reduction after 2 months was significantly greater. In the whole group, occupational stress was significantly correlated with the total number of symptoms and to some of the symptoms more specifically. As stress did not differ between highly- and lowly- exposed, there is no reason to assume an influence on the observed differences in the prevalence and reduction of symptoms. Conclusions: Our data suggest that MRI operators may experience various symptoms at the beginning of activity, rapidly reversible in a few weeks. The trend over longer periods deserves further study. Occupational stress may play a role in symptoms. The duration of previous MRI work (particularly short-term) as well as work-related stress should be adequately addressed in future studies on subjective symptoms in operators.